RESEARCH-BASED ENVIRONMENTAL LAW: THE DEBATE BETWEEN ECOLOGY VERSUS DEVELOPMENT - Irwansyah Irwansyah (Sriwijaya Law Review, 2017)
Nowadays, economic growth continues to be driven not followed by equity and justice compliance.Cases of natural resources looting, pollution and environmental destruction, forest fires and illegal mining, as well as the neglect of the rights of indigenous peoples, into a series of major issues and need study are not limited to mono-discipline approach. A research in the field of management and protection of natural resources and environment are more important to be used as a basic study was a paradigm shift from all stakeholders and policy-makers to synergize the importance of ecological with various dimensions. To realize the balance of ecological and development (economic) interests, have been used a wide variety of approach to environmental management in Indonesia, includes, command and control, self-regulation, voluntarism, education and information instruments, and economic instruments. As it turns out in practice, however it needed more consistent policies in applying the principles of sustainable development for the control and utilization of environmental resources.